DIVERSITY OF TREE SPECIES IN SYIAH KUALA UNIVERSITY - Djufri Djufri; Hasanuddin Hasanuddin; Abdullah Abdullah; Vivera Ruselli Puspa (Universitas Islam Negeri Ar-Raniry, 2022)
This research was conducted from April 2020 to October 2020 entitled